Affix rivalry: Theoretical and methodological challenges. (March 2023) - Huyghe, Richard; Varvara, Rossella
Abstract : Affix rivalry is a key element in the organization and evolution of derivational systems. Its study provides insight into word-formation semantics, morphological change, productivity, lexical variation, and the many-to-many relationship between form and meaning. Affix rivalry is characterized by its gradient nature and the multiplicity of factors that can be involved in its resolution. On the one hand, rival affixes can be regarded as more or less competing depending on their semantic similarity and on the proportion of semantic functions they have in common. On the other hand, the distinction between rival affixes can rely on different linguistic properties, including not only semantic, but also phonological, morphological, syntactic, stylistic, and sociolinguistic properties. Differences are observed as tendencies and have a variable influence on affix selection. Quantitative methods can be used to precisely assess degrees of rivalry and multifactorial resolution of competition. Based on the statistical analysis of large sets of derivatives, they can provide an accurate description of affix rivalry and help us better understand the mechanisms of competition in word formation.